Evaluation of a Full-Time Microsurgeon Educator on Resident Training, Research Collaboration, and Grant Funding - Donnelly, D'Andrea T.; Nicksic, Peter J.; Zeng, Weifeng; Dingle, Aaron M.; Poore, Samuel O. (Journal of Reconstructive Microsurgery, 2023)
Background The value of a fully trained microsurgeon dedicated to a laboratory setting at an academic institution is largely unknown. Microsurgery training lacks a national standard despite its highly complicated nature. Our study aims to evaluate the impact of a single laboratory-dedicated microsurgeon on the microsurgical training of integrated plastic surgery residents and collaborative efforts in research.Method We devised a three-faceted microsurgical training curriculum, including a collaborative multi-institutional microsurgery course, novel high-fidelity simulator models, and a dedicated microsurgeon. We cataloged grant funding achieved through support to other divisions' protocols. Time, in hours, spent on training and the number of anastomoses completed with the microsurgical educator in a laboratory setting over a 4-year period (2017–2021) were evaluated. Resident independence scores were collected from attending microsurgeons to quantify the translation of microsurgical training.Results Purchasing and maintenance costs of rats in our rodent facility decreased by $16,533.60 as 198 rats were replaced by our models. The residents who participated in our novel microsurgical training program were able to independently perform anastomoses in the OR by their postgraduate year 6. Additionally, the surgical support offered by our laboratory-dedicated microsurgeon led to a total of $24,171,921 in grant funding between 2017 and 2020.Conclusion Hiring an expert microsurgical educator to train residents in a laboratory has proved promising in accelerating microsurgical mastery. Novel training modules, alternatives to animal models, save resources in housing and animal costs. The addition of a research-oriented-microsurgeon has improved collaborative efforts to advance a range of surgical fields.
Keywords: education; simulation training; simulation models